Exploring the Quality of Life Perceptions among Chinese Tourists in Pokhara - Laxmi Kanta Sharma, (Journal of Development and Administrative Studies, 2024)
This study seeks to examine the influence of travel experiences in Pokhara on the Quality of Life (QoL) of Chinese tourists, with a focus on the notion that such experiences play a significant role in enhancing satisfaction across various dimensions of travel-related life domains. The investigation is grounded in the recollections of Chinese tourists following their most recent visit to Pokhara. To address the research objectives, a mixed-methods approach was employed. This involved conducting a survey of 400 Chinese tourists to assess their satisfaction levels and the importance ratings assigned to 14 key travel-related life domains, in addition to carrying out 25 in-depth interviews with Chinese tourists to gather qualitative insights. The data were analyzed using multiple regression analysis, which confirmed the study's hypothesis by demonstrating that both satisfaction and the importance ratings across the identified travel-related life domains significantly contribute to the overall life satisfaction of these tourists. The findings reveal that experiences in Pokhara substantially influence the QoL of Chinese tourists, affecting all assessed travel life domains. Based on these insights, the research concludes with practical recommendations for tourism operators in Pokhara. These strategies aim to enhance the well-being of Chinese tourists, thereby contributing to improved business performance and long-term sustainability within the local tourism sector.